HISTORICAL THEORETICAL FOUNDATIONS OF STATE ADMINISTRATION AND THE ISSUE OF LEADERSHIP PERSONNEL - Yuldashev, Avazbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article stressed about the concepts of state, governance and leadership and their content, their role in the coordination, organization, control, regulation, preservation and development of the social environment.